Administration According to the Principle of good governance of Municipality in the Eastern Region of Thailand: Administration According to the Principle of good governance of Municipality in the Eastern Region of Thailand - Lungcharoen, Somporn (RATANABUTH JOURNAL, 2023)
There are three objectives of this research: 1) to study the general state of good governance in municipalities in the eastern part of Thailand, 2) to study measures to prevent corruption in municipalities in the eastern part of Thailand. and 3) to find a form of management that uses desirable governance principles. 30 key informants. The tools used in the study were structured interviews. The results of the research were as follows: 1) Regarding the general situation regarding management according to the principles of good governance, it was found that most executives did not truly understand the principles of good governance. especially in the matter “Transparency” and “public participation”2) Regarding measures to prevent corrupt acts, it was found that local government organizations had clear policies and procedures that were clearly stated. Procedures are established that promote ethical behavior and hold employees accountable for their conduct. as well as encouraging the public to participate in various administrative activities of local government organizations3) Regarding the desirable governance-based management style, it was found that the management style should consist of the following: people-centered management. Community Knowledge Management Using a capable leader can actually manage and set high standards of performance.